Exercise intensity influences plasma and sweat amino acid concentrations: a crossover trial - Stone, M.; Clayton, Z. S.; Buono, M. J.; Kern, M. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The purpose of this study was to explore the relationship between concentrations of amino acid (AA) and related metabolites in plasma and sweat obtained before and after exercise performed at different intensities and therefore different rates of sweat loss. METHODS: Ten subjects completed a maximally ramped exercise test and three 30-min submaximal (45/60/75% VO2max) exercise bouts. Blood samples were collected before/after the exercise bouts and sweat was collected from the forearm throughout. Samples were analyzed for concentrations of AA and related molecules. RESULTS: Sweat AA excretion rate was higher during the 60% bout compared to the 45% bout but was similar in comparison to the 75% indicating a plateau in rates of sweat AA losses as sweat rate increased. Plasma concentrations of AAs, urea, ammonia, and other non-proteinogenic AAs were not significantly different between exercise bouts performed at 45% and 60%. Exercise at 75% tended to reduce concentrations of sweat amino acids with significantly depressed concentrations of glycine, lysine, serine, threonine, histidine, arginine, tryptophan, aspartate and ornithine. CONCLUSIONS: Overall, this research suggests that increasing exercise intensity increases AA metabolism as demonstrated by reduced plasma AA concentrations and increased excretion through sweat glands, which is mediated by a mechanism yet to be identified.